The book of silk / Philippa Scott. - Scott, Philippa (Thames & Hudson, 1993)
The Book of Silk tells the rich history of silk through five millennia, reproducing hundreds of fabrics, furnishings and garments from all parts of the world. It contains a reference section that includes terms and technical processes, and care.